Exploring Society's Views on Gender Role Reversal in Kudapan Spesial Movie: An Analysis Using Reception Analysis and Constructivism Paradigm - Kumala, Ajeng Dyah; Sukmono, Filosa Gita (CHANNEL: Jurnal Komunikasi, 2023)
Kudapan Spesial is a short film that explores the idea that women have equal influence and power as men. Gender, a cultural construct, is acquired and socialized in the family from an early age and is sometimes formed following the dominant culture. This study aims to ascertain how society views the frequent reversal of gender roles in the environment. This study examines how the audience creates meaning for the information communicated by the film Kudapan Spesial, using reception analysis and the constructivism paradigm. The data analysis process involves collecting data from informants, analyzing it, and understanding the dominant message in the film, followed by interviews to identify the informant's position. The study examined the film Kudapan Spesial using Umberto Eco's theory of sign formation and informant interviews. The film Kudapan Spesial was inspired by the director's personal experience of gender role exchange in his family. It features medium-long shots, warm lighting, and a tidy house representing the father's perspective. The film portrays varying perspectives on gender role exchange in Indonesian households, with some viewing it as hindering a wife's potential while others advocate for equal opportunities. The film 'Kudapan Spesial' has alternative concepts that intrigue audiences who view scenes and conflicts differently based on their backgrounds, experiences, and knowledge. The study on gender role interchange in families revealed that exposure to information and debate gained via the internet influences audiences' thinking. Further studies can examine gender roles' predominance in the family from a new perspective.